Miocardiopatia de etiologia isquémica versus não-isquémica: haverá diferenças no prognóstico? Experiência de um centro de insuficiência cardíaca avançada - Lourenço, C (2011)
INTRODUCTION: Previous studies have associated heart failure (HF) of ischemic etiology with worse prognosis compared to HF from non-ischemic cardiomyopathy. HF treatment has evolved significantly in recent years. Has this evolution had an impact on this prognostic gap? OBJECTIVE: The aim of our study was to compare patients with advanced HF--nonischemic versus ischemic etiology--in terms of baseline characteristics, treatment, and in-hospital and long-term prognosis (including death, heart transplantation and hospital readmission). METHODS: We performed a retrospective study including 286 consecutive patients with systolic HF admitted to an HF unit between January 2003 and June 2006. We compared two groups according to HF etiology: Group A--ischemic cardiomyopathy (n = 109); Group B--non-ischemic cardiomyopathy (n = 177). Mean follow-up was 41 months. RESULTS: Group A were older (62.2 +/- 10.4 vs. 55.9 +/- 15.2 years, p < 0.001), with a higher proportion of males (80.7 vs. 67.8%, p = 0.017), diabetes, anemia, dyslipidemia and smokers; they required more prolonged treatment with inotropic drugs and more frequent treatment with statins, antiplatelet agents and nitrates. On admission, Group B patients presented with lower serum sodium and higher aminotransferase levels. There were no differences in the occurrence of cardiogenic shock or dysrhythmias, baseline ECG rhythm, frequency of left bundle branch block, renal function, BNP, left ventricular ejection fraction, heart rate or implantation of intracardiac devices. Group A had higher in-hospital mortality (11.0 vs. 4.0%, p = 0.020). Multivariate analysis showed that the only predictor of in-hospital mortality was serum sodium < 133 mmol/l and also showed that HF etiology was not a predictor of this endpoint; previous medication with angiotensin-converting enzyme inhibitors was a protective factor. On Kaplan-Meier analysis, it was observed that, in the long-term, there were no significant differences in either survival rates (70.0 vs. 76.8%, p = 0.258), or the combined endpoints of survival free of death or heart transplantation (55.7 vs. 54.5%, p = 0.899) and survival free of death, heart transplantation or hospital readmission (38.0 vs. 32.8%, p = 0.386). CONCLUSIONS: Although in-hospital mortality was higher in ischemic cardiomyopathy, this variable was not an independent predictor of mortality and the difference appears to fade in the long-term, in contrast to what had been reported in older studies, but in agreement with more recent data